2019
DOI: 10.1155/2019/6935147
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Targets Participating in Myocardial Ischemia-Reperfusion Injury and Cardioprotection

Abstract: Worldwide morbidity and mortality from acute myocardial infarction (AMI) and related heart failure remain high. While effective early reperfusion of the criminal coronary artery after a confirmed AMI is the typical treatment at present, collateral myocardial ischemia-reperfusion injury (MIRI) and pertinent cardioprotection are still challenging to address and have inadequately understood mechanisms. Therefore, unveiling the related novel molecular targets and networks participating in triggering and resisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 158 publications
0
32
0
1
Order By: Relevance
“…Previous studies have shown that the prevention and treatment of Miri depends on the following features: i) Simply targeting sham, control sham group; i/r, ischemic and reperfusion; ad-r, ad-rP105 group; ad-r-sirna, ad-rP105-sirna group; ad-G-sirna, ad-eGFP-sirna group; Tlr2/4, Toll-like receptor 2/4; TnF-α, tumor necrosis factor; il-6, interleukin 6; Md2, myeloid differentiation protein 2; iP, immunoprecipitation. the protective gene or harmful gene; ii) interfering with the expression of a single gene to play a comprehensive role in multiple pathogenic processes; or iii) modulating the expression of target genes via non-coding rnas (27,28). although these strategies provide novel ways to alleviate Miri, the clinical effect is still unsatisfactory (22,24,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the prevention and treatment of Miri depends on the following features: i) Simply targeting sham, control sham group; i/r, ischemic and reperfusion; ad-r, ad-rP105 group; ad-r-sirna, ad-rP105-sirna group; ad-G-sirna, ad-eGFP-sirna group; Tlr2/4, Toll-like receptor 2/4; TnF-α, tumor necrosis factor; il-6, interleukin 6; Md2, myeloid differentiation protein 2; iP, immunoprecipitation. the protective gene or harmful gene; ii) interfering with the expression of a single gene to play a comprehensive role in multiple pathogenic processes; or iii) modulating the expression of target genes via non-coding rnas (27,28). although these strategies provide novel ways to alleviate Miri, the clinical effect is still unsatisfactory (22,24,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…cardiovascular diseases (cVds) are a common threat to human health and were the leading cause of human mortality between 2009 and 2011 worldwide (1,2). Ischemic heart disease, which accounts for a large subset of cVds, leads to hypoxia and, ultimately, cardiomyocyte death (3). Timely reperfusion is the main therapeutic strategy to resuscitate the ischemic or hypoxic myocardium (4).…”
Section: Introductionmentioning
confidence: 99%
“…Набуті вади серця На сьогодні однією з найважливіших проблем у серцево-судинній хірургії, що потребує подальшого дослідження, є забезпечення адекватного інтраопераційного захисту міокарда. Виділяють декілька різноманітних підходів проведення захисту міокарда, які мають свої переваги й недоліки [3,4]. Не існує єдиного, загальновизнаного протоколу при корекції поєднання багатоклапаного ураження з ІХС.…”
Section: український журнал серцево-судинної хірургії 2019 4 (37)unclassified